Cephalopod Brains: An Overview of Current Knowledge to Facilitate Comparison With Vertebrates - Shigeno, Shuichi; Andrews, Paul L. R.; Ponte, Giovanna; Fiorito, Graziano (Frontiers in Physiology, 2018)
Cephalopod and vertebrate neural-systems are often highlighted as a traditional example of convergent evolution. Their large brains, relative to body size, and complexity of sensory-motor systems and behavioral repertoires offer opportunities for comparative analysis. Despite various attempts, questions on how cephalopod ‘brains’ evolved and to what extent it is possible to identify a vertebrate-equivalence, assuming it exists, remain still unanswered. Here, we summarize recent molecular, anatomical and developmental data to explore certain features in the neural organization of cephalopods and vertebrates to explore to what extent an evolutionary convergence is likely. Furthermore, and based on whole body and brain axes as defined in early-stage embryos using the expression patterns of homeodomain-containing transcription factors and axonal tractography, we describe a critical analysis of cephalopod neural systems exploring similarities with the cerebral cortex, thalamus, basal ganglia, midbrain, cerebellum, hypothalamus, brain stem and spinal cord of vertebrates. Our overall aim is to promote and facilitate further, hypothesis-driven, studies of cephalopod neural systems evolution.